Changes in the lipidome in type 1 diabetes following low carbohydrate diet: Post‐hoc analysis of a randomized crossover trial. Issue 2 (4th January 2021) - Al‐Sari, Naba; Schmidt, Signe; Suvitaival, Tommi; Kim, Min; Trošt, Kajetan; Ranjan, Ajenthen G.; Christensen, Merete B.; Overgaard, Anne J.; Pociot, Flemming; Nørgaard, Kirsten; Legido‐Quigley, Cristina
Abstract: Aims: Lipid metabolism might be compromised in type 1 diabetes, and the understanding of lipid physiology is critically important. This study aimed to compare the change in plasma lipid concentrations during carbohydrate dietary changes in individuals with type 1 diabetes and identify links to early‐stage dyslipidaemia. We hypothesized that (1) the lipidomic profiles after ingesting low or high carbohydrate diet for 12 weeks would be different; and (2) specific annotated lipid species could have significant associations with metabolic outcomes. Methods: Ten adults with type 1 diabetes (mean ± SD: age 43.6 ± 13.8 years, diabetes duration 24.5 ± 13.4 years, BMI 24.9 ± 2.1 kg/m 2, HbA1c 57.6 ± 2.6 mmol/mol) using insulin pumps participated in a randomized 2‐period crossover study with a 12‐week intervention period of low carbohydrate diet (< 100 g carbohydrates/day) or high carbohydrate diet (> 250 g carbohydrates/day), respectively, separated by a 12‐week washout period. A large‐scale non‐targeted lipidomics was performed with mass spectrometry in fasting plasma samples obtained before and after each diet intervention. Longitudinal lipid levels were analysed using linear mixed‐effects models. Results: In total, 289 lipid species were identified from 14 major lipid classes. Comparing the two diets, 11 lipid species belonging to sphingomyelins, phosphatidylcholines and LPC(O‐16:0) were changed. All the 11 lipid species were significantly elevated during low carbohydrate diet. Two lipid species were most differentiated between diets, namely SM(d36:1) (β ± SE: 1.44 ± 0.28, FDR  = 0.010) and PC(P‐36:4)/PC(O‐36:5) (β ± SE: 1.34 ± 0.25, FDR  = 0.009) species. Polyunsaturated PC(35:4) was inversely associated with BMI and positively associated with HDL cholesterol (p < .001). Conclusion: Lipidome‐wide outcome analysis of a randomized crossover trial of individuals with type 1 diabetes following a low carbohydrate diet showed an increase in sphingomyelins and phosphatidylcholines which are thought to reduce dyslipidaemia. The polyunsaturated phosphatidylcholine 35:4 was inversely associated with BMI and positively associated with HDL cholesterol (p < .001). Results from this study warrant for more investigation on the long‐term effect of single lipid species in type 1 diabetes. Abstract : This study demonstrates that unsaturated phosphatidylcholines and monounsaturated sphingomyelins were elevated with diet in individuals with type 1 diabetes following low carbohydrate diet.